Maize stalk rot caused by Fusarium graminearum alters soil microbial composition and is directly inhibited by Bacillus siamensis isolated from rhizosphere soil - Zhang, Kang; Wang, Liming; Si, Helong; Guo, Hao; Liu, Jianhu; Jia, Jiao; Su, Qianfu; Wang, Yanbo; Zang, Jinping; Xing, Jihong; Dong, Jingao (Frontiers in Microbiology, 2022)
Maize stalk rot caused by Fusarium graminearum can reduce the yield of maize and efficiency of mechanized harvesting. Besides, deoxynivalenol and zearalenone toxins produced by F. graminearum can also affect domestic animals and human health. As chemical fungicides are expensive and exert negative effects on the environment, the use of biological control agents has become attractive in recent years. In the present study, we collected rhizosphere soil with severe stalk rot disease (ZDD), the rhizosphere soil with disease-free near by the ZDD (ZDH), and measured rhizosphere microbial diversity and microbial taxonomic composition by Illumina high-throughput sequencing. The results showed that Fusarium stalk rot caused by the F. graminearum would significantly reduce the abundance and alpha diversity of rhizosphere microbial community, and shift the beta diversity of microorganisms. Furthermore, a bacterial strain, Bacillus siamensis GL-02, isolated from ZDD, was found to significantly affect growth of F. graminearum. In vitro and in vivo assays demonstrated that B. siamensis GL-02 had good capability to inhibit F. graminearum. These results revealed that B. siamensis GL-02 could be a potential biocontrol agent for the control of maize stalk rot.